Drifting in the deep: Metatranscriptomics and metabarcoding reveal sustained metabolic activity and community composition in hydrothermal vent plume microbial communities - Polinski, Jennifer M.; Rodrigue, Mattie; Meyer, Jason D.; Harke, Matthew J. (Frontiers in Marine Science, 2023)
The deep sea is the largest habitat on our planet, supporting a vast diversity of organisms which have yet to be fully described. This habitat is punctuated by hydrothermal vents in which energy derived from chemosynthesis drives carbon fixation, supporting a complex and rich food web. Connectivity between vent systems remains an active area of research, with questions as to how vent-influenced microbial function and diversity persists over space and time. In particular, the role hydrothermal vent plumes play as potential highways for connectivity and biogeography is not well understood. To add to the growing body of research, this study sampled plume waters above the Moytirra hydrothermal vent field, located just north of the Azores. We examined how hydrothermal vent plume community biodiversity and metabolic activities change with distance from the vent using a combination of metabarcoding and metatranscriptomic sequencing. We detected a rich diversity of both prokaryotic and eukaryotic organisms inhabiting the plume, which remained metabolically active for kilometers from the vent source. Enriched sulfur metabolism functional signals and relative abundance of sulfur oxidizing bacteria suggest reduced sulfur compounds are a fundamental energy source within plume waters. Additionally, we observed evidence of top-down controls on primary production through both known grazers and putative viral activity. Although community-level functional signals suggest active metabolic functions for over a kilometer north or south of the vent field, these functions grew increasingly dissimilar to those observed directly above the vent site, and bacterial communities displayed indications of entering quiescent stages, likely due to decreasing resources and reduced temperatures. These data provide a first glimpse of Moytirra’s microbial biodiversity, in addition to providing a high-resolution understanding of life on the drift within a hydrothermal plume, its persistence with distance, and implications for connectivity.